Sei sulla pagina 1di 2

Trasformate di Laplace.

Z
f (t) causale

F (s) = L(f )(s) =

f (t)est dt

H(t)
H(t)tn
t1
()
et et
H(t)

H(t)et

H(t) sin t
H(t) cos t
H(t) sinh t
H(t) cosh t
H(t) log t
2

H(t)et

H(t) erf(t)

H(t) erf( t)
H(t)J0 (at)

H(t)J0 (2 at)

1
s
n!
sn+1
1
(s )
1
(s )(s )

2
s + 2
s
s2 + 2

s2 2
s
2
s 2
0 (1) log s
s

s2 /4
e
erfc(s/2)
2
1 s2 /4
e
erfc(s/2)
s
1

s s+1
1

2
s + a2
s/a
e
s

nN
Re > 0, C
, C, 6=
6= 0
6= 0
6= 0
6= 0

a>0
a>0

La funzione di Eulero.
+

t1 et dt,

() :=

Re > 0;

C \ {0, 1, 2, . . . , n, . . . , }

( + 1) = (),

(n) = (n 1)! n = 1, 2, . . .
( 12 ) =

1 3 5 . . . (2n 1)
(2n)!
= 2n

n
2
2 n!

()(1 ) =
sin
n
X
1
0
(1) = = lim log n
n+
k

(n + 1/2) =

k=1

Error functions
erf t =

s2

ds,

erfc t = 1 erf t =

Funzioni di Bessel.

J (t) :=

+
X
n=0

J00

(x/2)

(1)n (x/2)2n
n!(n + + 1)

+ 1t J0 + (1

2
t2 )J

=0

Z
t

es ds